The Power of Practicum Support: A Quasi-experimental Investigation of Elementary Preservice Teachers' Science Instruction in A Highly Supported Field Experience. Issue 4 (19th May 2022) - Kruse, Jerrid; Wilcox, Jesse; Patel, Neal; Borzo, Sarah; Seebach, Colin; Henning, Joleen
ABSTRACT: This study sought to determine the impact of a highly supported field experience (HSFE) by comparing two groups of preservice elementary teachers (PSETs) all taking the same methods course, from the same instructor, within the same program. Each group was required to complete a 10-hour field experience. One group was in a HSFE while the other group was placed in "unsupported" placements. Findings indicate that the HSFE group enacted statistically significant and far more effective science instruction than the unsupported group. Possible reasons for the difference and implications for teacher education are discussed.